Effect of the immersion moment at the volumetric alteration of the mineral trioxide aggregate HP - Canali, Lyz Cristina Furquim; Zancan, Rafaela Fernandes; Vivan, Rodrigo Ricci; Filho, Mario Tanomaru [UNESP]; Duarte, Marco Antonio Hungaro (Dental Press International, 2021)
Introduction: Solubility is a property related to the dissociation of the constituents of the material by the action of contact with the surrounding liquid, for this reason, the aim of this study was to evaluate the effect of the hydration during the scanning in the microtomography on the volumetric alteration of the MTA HP. Methods: Twenty acrylic teeth upper incisor with retrograde cavity were utilized. The MTA HP cement was inserted into the cavity using a Paiva condensor. The specimens were visually inspected with a 5x magnifying glass to ensure they did not remain void or gaps. The specimens were divided into 2 groups (n=10). The teeth were scanned shortly after handling the MTA. For the group with water immersion, hydrated Eppendorf was kept with 1mL the water during the scanning and the other group, the teeth were scanning without water. In the two groups the teeth were immersed into water during 7 days. Next the teeth were newly scanned in the Micro-CT using the same parameters and conditions of each group. Reconstruction of images by the Nrecon software and the solubility volume determined by the CTan, analyzing the volumetric change. Results: The group of specimens scanned immersed into the water presented higher volumetric change with statistically significant differences in relation the group scanned without immersion. The scanning of the specimen immersed in water favors the greater volumetric loss of the material. Conclusion: Studies to evaluate volumetric change of calcium silicate cements should be made immersed in water
Keywords: Physical and chemical properties; Root canal obturation; Solubility